Real-world effectiveness of treatments for type 2 diabetes, hypercholesterolemia, and hypertension in Canadian routine care – Results from the CardioVascular and metabolic treatment in Canada: Assessment of REal-life therapeutic value (CV-CARE) registry, 12-months results. (December 2020) - Goldenberg, Ronald; Bell, Alan; Cheng, Willoon; Fils-Aimé, Nadège; Burrows, Melonie; Blavignac, Jessica; Parron, Emilia; Barakat, Maxime
Highlights: Achieving targets of cardiometabolic disease parameters crucial to delay complications. RWE of the safety and efficacy of CV and metabolic drugs in Canada is scarce. CV-CARE provides RWE in Canadian routine clinical care setting. Abstract: Aims: The CV-CARE registry provides RWE in Canadian routine clinical practice. Methods: CV-CARE is a multi-site, observational, prospective Canadian registry enrolling patients initiating treatment with metformin hydrochloride extended-release (MetER) for T2D; colesevelam (C) for HCh; and azilsartan (AZI), azilsartan/chlorthalidone (AZI/CHL) or diltiazem extended-release (TXC) for HTN. Patient characteristics/assessment were performed at baseline and 12 ± 6 months. Primary outcome was absolute change in HbA1c and FPG (MetER); % change in LDL-C (C); and absolute change in BP (AZI-AZI/CHL-TXC). Results: Of the 4194 patients in the primary analysis population, 24% were taking MetER, 39% were taking C, 33% were taking AZI, 12% were taking AZI/CHL, and 3% were taking TXC. At 12 months, MetER-treated patients had an absolute mean (95% CI) change in HbA1c of −0.3% [−0.4; −0.2] and in FPG of 0.7 mmol/L [−1.0; −0.4]. C-treated patients had a mean (95% CI) % change in LDL-C of −13.0% [−14.6; −11.4]. Absolute mean (95% CI) changes in SBP were −18.7 mmHg [−19.7; −17.7](AZI), −21.3 mmHg [−23.1; −19.5](AZI/CHL), and -12.3 mmHg [−15.1; −9.6](TXC). Conclusion: In a real-world Canadian setting, MetER, C, AZI, AZI/CHL, and TXC show improvement of the cardiometabolic profile of T2D, HCh, and HTN patients.